If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(y + 4) = 36 Reorder the terms: -1(4 + y) = 36 (4 * -1 + y * -1) = 36 (-4 + -1y) = 36 Solving -4 + -1y = 36 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1y = 36 + 4 Combine like terms: -4 + 4 = 0 0 + -1y = 36 + 4 -1y = 36 + 4 Combine like terms: 36 + 4 = 40 -1y = 40 Divide each side by '-1'. y = -40 Simplifying y = -40
| X+4=4(1-X)+5x | | .65x=25 | | -6t=60+10t | | N=8*3.14 | | 4.5x-1=3.5x | | 9x-8=9x | | 6-9x=7x-10x-12 | | 5x-4+2x-8=16 | | 7x-7=4x+3+8x | | 0.2y+3=0.67 | | 5x-3.5=15.25 | | e-x=8 | | -8-6p=-6p-4 | | -58m=-7(m+6)+2(3m-8) | | x+.05x=39375 | | -12x+27=-24 | | 31+6=113 | | x-9u+18=0 | | -2x-4+3x=10+5x-2 | | 6+31=113 | | 7x+6x-84=42-8x | | 45=8(x-5) | | -12x+27=24 | | 9-5z=12-(z+7) | | 8y+11=6y+11 | | 11-13/15x=209 | | 7(x-7)+4x=-2(x+5) | | 3(12+10)=36x-8 | | x-.25x=30 | | 11x+4=11x-9 | | 6-x=4x-9 | | 1.5x+4.1=-2.8 |